Mapping the Potential of Corporate Social Responsibility (CSR) Programs in Palm Oil Plantations - Agus Manto; Sri Gunawan (Tropical Plantation Journal, 2026)
The oil palm plantation industry adheres to the concept of sustainability paradigm on 3 main principles, namely profit, people (social society) and planet (environment). One of the social issues is to keep community involvement in running the oil palm plantation business process stable. With the existence of social problems in the community regarding oil palm plantations, the company as a stakeholder seeks to implement Corporate Social Responsibility (CSR) programs with the hope of establishing a harmonious relationship between the company and the local community and the establishment of cooperation so that the community benefits both socially, economically and culturally. This potential mapping program is expected to be the foundation for oil palm plantation companies to determine appropriate coaching programs to improve the welfare of the community around the company by analyzing the description of production aspects, market aspects, administrative financial aspects, human resource aspects, sustainability aspects in each potential business. The research is focused on 2 sub-districts and 1 district in the province of Central Kalimantan. From the results of the analysis , it was concluded that the potential for CSR for horticulture committees and fisheries and livestock commodities became a priority program due to limited needs and supplies.